Global sport and the Gulf’s sovereign wealth funds - Koch, Natalie (Aspenia online, 2022)
Newcastle United’s takeover in October 2021 by a consortium that would give Saudi Arabia’s sovereign wealth fund, the Public Investment Fund (PIF), an 80% stake in the club brought renewed attention to the role of Gulf money in European sports. The £
Gesehen am 08.12.2022